Floral morphology, micromorphology and palinology of selected Sedum s.l. species (Crassulaceae). (4th May 2018) - Giuliani, C.; Foggi, B.; Mariotti Lippi, M.
Abstract: Sedum L. (Crassulaceae) is a large and taxonomically difficult genus whose delimitation and classification are under debate. Due to the controversial results of previous cytological, morphological, and molecular studies, further investigations are needed in order to gain a shared taxonomy of the current recognized species clades. In the present paper, morphological and micromorphological features of 23 selected Mediterranean species of Sedum s.l . – collected from exsiccata or fresh specimens throughout Italy – were investigated, in order to provide additional data toward their classification above species level. In particular, the study focused on flower structure and morphology, floral epidermal surfaces and pollen morphology. The distribution pattern of the examined microcharacters across the species revealed a wide range of variation and different combinations of the single characters. NMDS analysis allowed individuating discrete groups that showed a general consistency with the current systematic delimitation of species groups. Our study also evidenced for the first time the wide morphological variability of nectaries and of the glandular indumentum, not previously investigated in detail. In addition, we proposed the combined use of floral diagrams and floral formulae as valuable tools in studying the variability of flower structure at genus level.